Updated Checklist of Arthropods from Azores (Portugal) - Borges, Paulo A. V. (2022)
The data we present consists in an updated checklist of the Azorean arthropods. The checklist compile known records based on published literature, unpublished data, and new records at archipelago and island levels. This publication represents the most recent information about distribution of introduced, native and endemic arthropods in the Azores archipelago. Currently the total number of terrestrial arthropod taxa (species and subspecies) in the Azores is estimated of about 2417 belonging to 14 classes, 53 orders, 438 families, 1554 genera and 2397 species and 149 individual subspecies. The most diverse orders of Azorean arthropods are: Coleoptera (585 taxa), Diptera (422 taxa), Hemiptera (338 taxa), Hymenoptera (162 taxa), Lepidoptera (159 taxa) and Araneae (132 taxa). A total of 275 endemic taxa are currently known (231 species and 44 subspecies), belonging to 8 classes and 22 orders. São Miguel, Terceira and Pico are the islands with higher number of endemic species and subspecies. Compared to the other nearest Macaronesian archipelagos (Madeira and Canaries), the Azorean arthropod fauna is characterized by a lower percentage of endemism and a high proportion of exotic introduced species.